Current global issues from the perspective of preservice teachers: How are they illustrated in cartoons? - Kayaalp, Fatih; Başçı Namlı, Zeynep; Meral, Elif (Pegem Journal of Education and Instruction, 2021)
The aim of this study is to examine how the mental images in the minds of preservice social studies teachers regarding current global issues are illustrated in the cartoons they draw. The phenomenological research design was used in the present study, which was conducted with 39 preservice social studies teachers, who had previously taken the ‘Current Global Issues’ course. The data were collected through the cartoon-making activity forms prepared by the researchers and analysed using the content analysis technique. The results showed that the cartoons that activate the questioning as well as critical and creative thinking processes of preservice teachers on current global issues are influential in the way they express their ideas about an issue, and that the problems are likely to be discussed from a broader perspective. The problems addressed appeared to be related to both environmental and social issues. Among the major problems, environmental issues such as environmental pollution, global warming, and drought were found to have been frequently illustrated in the cartoons, in addition to a social problem pertaining to the health concerns caused by the impact of the COVID-19 pandemic. Such problems as technology addiction, wars, and violence were also observed in the cartoons as part of social concerns.